2021
DOI: 10.1039/d1sc04755h
|View full text |Cite
|
Sign up to set email alerts
|

A single-atom Cu–N2catalyst eliminates oxygen interference for electrochemical sensing of hydrogen peroxide in a living animal brain

Abstract: We have achieved the selective monitoring of H2O2 fluctuation in vivo free from O2 interference by a single-atom Cu–N2 electrocatalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 72 publications
(67 reference statements)
0
35
0
Order By: Relevance
“…Beneting from the atomically dispersed metal active centers, single-atom catalysts (SACs) have the maximum extent of metal dispersion and atomic utilization, and have become the most promising materials to realize the rational utilization of metal resources and atomic economy. [25][26][27] The strong interaction between metal atoms and carrier materials is very signicant for keeping the atomic dispersion of metal active centers and preventing agglomeration into particles. [28][29][30][31] Carbon materials have been proven to be ideal carrier materials because of their adjustable structure, excellent conductivity, stable physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Beneting from the atomically dispersed metal active centers, single-atom catalysts (SACs) have the maximum extent of metal dispersion and atomic utilization, and have become the most promising materials to realize the rational utilization of metal resources and atomic economy. [25][26][27] The strong interaction between metal atoms and carrier materials is very signicant for keeping the atomic dispersion of metal active centers and preventing agglomeration into particles. [28][29][30][31] Carbon materials have been proven to be ideal carrier materials because of their adjustable structure, excellent conductivity, stable physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Various earth-abundant transition metal-based compounds have aroused intensive research interest as alternatives, and nowadays some of them have shown considerable performance. [10][11][12][13] However, dynamic reconstruction usually occurs in most these compounds under working processes, which makes it hard to recognize really catalytic origins and structure-property relationships. [14] Therefore, studying dynamic reconstruction, despite being challenging, opens a novel avenue to uncover catalytic mechanisms and develop design principles toward highperformance catalysts.…”
mentioning
confidence: 99%
“…In fact, electrochemical sensing of H 2 O 2 can avoid oxidative decomposition interferences from common chemical and biochemical interfering species. However, the oxygen reduction reaction (ORR) of dissolved oxygen in the solution at a similar reductive potential is a major challenge to the electrochemical sensing of H 2 O 2 . Currently, most of the reported H 2 O 2 electrochemical sensors are tested in degassed electrolytes protected by inert or nitrogen atmospheres. To avoid interference from ORR under ambient conditions, a reasonable electrochemical sensing window is necessary.…”
Section: Resultsmentioning
confidence: 99%